Pengembangan Materi Ajar Pendidikan Islam Bernuansa Adat Basandi Syara’, Syara’ Basandi Kitabullah Bagi Narapidana di Rutan Kota Padang Panjang - Hubban Jamma; Duski Samad; Muhammad Zalnur (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
A prisoner is someone who is serving a sentence in a detention center. This research aims to: 1) describe Islamic Education teaching materials in the Padang Panjang City State Detention Center. 2) Developing Islamic Education Teaching Materials with the nuances of Adat Basandi Syara', Syara' Basandi Kitabullah (ABS SBK). 3) Revealing the validity, practicality and effectiveness of the development of Islamic Education Teaching Materials with the nuances of Adat Basandi Syara', Syara' Basandi Kitabullah (ABS SBK). This research is a development research or Research and Development (R&D) with research steps referring to the 4-D development model. The findings in this study are: 1) Islamic Education Teaching Materials at the Padang Panjang City State Detention Center have not been properly arranged in accordance with teaching material components such as a) KI and KD analysis, b) Material Title and Indicators and Objectives, c) Material Outline, d) References, and e) Illustrations of Images, Tables, Diagrams. 2) Based on experiments, Islamic Education Teaching Materials with the nuances of Adat Basandi Syara', Syara' Basandi Kitabullah (ABS SBK) can be applied in all Islamic Education teaching materials. 3) The validity, practicality and effectiveness tests show that the Islamic Education Teaching Materials with the nuances of Adat Basandi Syara', Syara' Basandi Kitabullah (ABS SBK) are very valid, practical and effective.